037 A data-driven assessment of the proposed criteria for classification of primary progressive aphasia. Issue 3 (9th February 2012) - Sajjadi, S A; Patterson, K; Tomek, M; Arnold, R J; Nestor, P J
Abstract : Primary progressive aphasia (PPA), a neurodegenerative syndrome characterised by gradual dissolution of language, is both clinically and pathologically heterogeneous. Identification of discrete clinical subtypes has been considered relevant to predicting underlying pathology. The latest consensus criteria recognise three variants and propose a diagnostic framework based primarily upon clinical and neuropsychological findings. We hypothesised that a significant proportion of PPA patients would not fulfil the criteria for any of these variants. 41 PPA patients were prospectively recruited to a longitudinal study. All patients had detailed assessments testing all proposed diagnostic domains. 12, 9, and 4 patients fulfilled the criteria for semantic, non-fluent, and logopenic variants, respectively. 16 patients (39%), however, had features overlapping these variants and could only be labelled mixed PPA. There was no statistical difference between the age, education, disease duration, and dementia severity of the different groups. Factor analysis using consensus-proposed neuropsychological measures showed clustering of the markers along the expected axes. By plotting the patients against their factor scores, we found that mixed PPA subjects were scattered amongst relatively discrete pockets of semantic, logopenic, and non-fluent subjects. Our data driven results suggest that cases which defy the current tripartite classification represent the largest proportion of PPA patients.